1997
DOI: 10.1038/bjc.1997.23
|View full text |Cite
|
Sign up to set email alerts
|

Oral contraceptive use at a young age and the risk of breast cancer: an Icelandic, population-based cohort study of the effect of birth year

Abstract: Summary The possible association between breast cancer and oral contraceptive use before the age of 20 was investigated using Icelandic population-based information from women born after 1944. The design was a nested case-control study within a cohort, using data on duration of oral contraceptive use at young ages. The availability of oral contraceptives before the age of 20 has changed dramatically and is highly dependent on birth years, with 20% and 82% starting before the age of 20 among Icelandic users bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…A previous Icelandic study focusing on OC use at young ages and therefore using information given at the first visit to the CDC and only from birth cohorts who had the possibility of exposure to OCs from an early age, indicated a dose-response relationship between breast cancer risk and duration of OC use in young users. 29 The present study group was stratified according to age at diagnosis with cutting points Ͻ40, 40 -55 and Ͼ55 years at diagnosis, where the oldest group represented women diagnosed at postmenopausal ages. The data were also analyzed with stratification according to menopausal status, giving similar results except that this did not allow for investigating separately women diagnosed under the age of 40.…”
Section: Discussionmentioning
confidence: 99%
“…A previous Icelandic study focusing on OC use at young ages and therefore using information given at the first visit to the CDC and only from birth cohorts who had the possibility of exposure to OCs from an early age, indicated a dose-response relationship between breast cancer risk and duration of OC use in young users. 29 The present study group was stratified according to age at diagnosis with cutting points Ͻ40, 40 -55 and Ͼ55 years at diagnosis, where the oldest group represented women diagnosed at postmenopausal ages. The data were also analyzed with stratification according to menopausal status, giving similar results except that this did not allow for investigating separately women diagnosed under the age of 40.…”
Section: Discussionmentioning
confidence: 99%
“…23,27,28 Early oral contraceptive use has a modest effect on breast cancer risk in young women. 29,30 Another study showed that there was an odds ratio of 2.39 for Her-2/neu-positive versus Her-2/neu-negative tumors in women younger than 45 years who had taken oral contraceptives. 31 Parity, particularly early age at first full-term pregnancy combined with higher overall parity, has been hypothesized to explain some of the elevated incidence of breast cancer among young African-American women.…”
Section: Hormones and Hormonal Risk Factorsmentioning
confidence: 99%
“…In addition, studies have shown that African-American breast cancer patients have unique BRCA1 gene mutations, that there are no racial differences in polymorphic distributions of CYP17, and that young women have frequent allelic loss at 11q24.1-q25, which is associated with poor survival rates. 23,30,[35][36][37][38][39][40][41][42][43][44][45] …”
Section: Geneticsmentioning
confidence: 99%
“…Some of the later studies concluded that OC use is a risk factor for breast cancer [3-10], or is for some subgroups [11,12], while other studies have not [13-16]. Young women having used the pill for a long time before their first pregnancy have been identified as a potential risk group [6,14,17,18], but currently there are not enough studies to prove or disprove the increased risk of breast cancer [19]. …”
Section: Introductionmentioning
confidence: 99%